1992
DOI: 10.1086/629626
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Tsunami Sedimentation on the Southeastern Coast of Australia

Abstract: In the coastal region, the highest magnitude storms cannot always be invoked to account for large-scale, anomalous sediment features. Any coastline in the Pacific Ocean region can be affected by tsunamis, including Australia which historically lacks evidence of such events. Geologically, tsunamis along the New South Wales coast have deposited a suite of Holocene features that consist of anomalous boulder masses, either chaotically tossed onto rock platforms and backshores or jammed into crevices; highly bimoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(54 citation statements)
references
References 19 publications
0
50
0
4
Order By: Relevance
“…In Australia, megatsunamis are responsible for shaping headlands and spreading sediment kilometers inland, in some cases tens of meters in thickness (Bryant et al 1992(Bryant et al , 1997Bryant and Nott 2001;Nott and Bryant 2003). In the Caribbean, tsunamis are responsible for the deposition of boulder ridges along the coast and the transport of boulders hundreds of meters inland (Scheffers 2002(Scheffers , 2004Scheffers et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, megatsunamis are responsible for shaping headlands and spreading sediment kilometers inland, in some cases tens of meters in thickness (Bryant et al 1992(Bryant et al , 1997Bryant and Nott 2001;Nott and Bryant 2003). In the Caribbean, tsunamis are responsible for the deposition of boulder ridges along the coast and the transport of boulders hundreds of meters inland (Scheffers 2002(Scheffers , 2004Scheffers et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…On the assumption that the materials were well exposed to light before transport for long enough to reset the dating`c lock'' and were then covered by tidal or other deposits, they can be dated. Bryant et al (1992) found evidence for tsunami sedimentation on the south-east coast of Australia, with TL ages of several events since 3 ka BP. Wood (1994) has also described boulder deposits consistent with storm surges or tsunami in Tunisia and has found coarse grain quartz GLSL ages for the deposit and its surroundings.…”
Section: Sediments and Their Associationsmentioning
confidence: 96%
“…Ces dépôts très grossiers sont le résultat de dynamiques marines de très forte énergie et leur mise en place a deux origines possibles. Sur le pourtour du Pacifi que et en Méditerranée, plus généralement dans les régions caractérisées par une forte activité sismique leur présence est plutôt attribuée à l'action de vagues géantes de « tsunamis » (Clague et al, 1999 ;Atwater, 1992 ;Atwater et Moore, 1992 ;Bryant et al, 1992 ;Young et al, 1996 ;Goff et al, 2001 ;Nichol et al, 2003 ;Pinegina et Bourgeois, 2001 ;Mastronuzzi et Sansò, 2004 ;Mastronuzzi et al, 2006Mastronuzzi et al, , 2007Scicchitano et al, 2007 ;Vott et al, 2008 ;Maouche et al, 2009). Dans le nord et nord-est de l'Atlantique ces dépôts ont été étudiés en Irlande, sur les îles d'Aran (William et al, 2004 ;Hall et al, 2006), sur les îles des archipels de l'Écosse (Orkney et Shetland Islands) Hall et al, 2008), et en Islande (Étienne et Paris, 2009), où leur origine a été attribuée à des événements météo-marins extrêmes de type tempêtes ou ouragans (Hansom et Barltrop, 2008 ;Hansom et al, 2009).…”
Section: Depth and Velocity Suffi Cient To Transport Blocks All The Wunclassified